The importance of the dental surgeon’s knowledge of parasitology for the treatment of oral myiasis (Research, Society and Development, 2022)
Objective: To demonstrate through this literature review the importance of knowledge of general parasitology during the duration of dentistry for oral treatment. Methodology: This is an integrative literature review, in order to characterize and analyze the dentist's knowledge in oral cases. A scientific search was carried out in the databases SciElo, Medline, PubMed, BvS and published books, using the following descriptors: “dentistry”, “parasitology”, “maxillofacial” and “myiasis”. Results: The authors point out that these parasites are turned from the larvae of Hominivorax flies and that the site most closely related to oral myiasis is the anterior region of the jaws. Conclusion: Myiasis mainly affects patients in oral socioeconomic conditions and with poor oral hygiene.